Thrombocytosis and bleeding in myeloproliferative neoplasms: exploring clinical diversity and risk of acquired von Willebrand syndrome—insights from a UK center - Giulia Simini; Andrew Innes; Saravanan Vinayagam; Golzar Mobayen; Nilanthi Karawitage; Simone Claudiani; Zain Odho; Mike Laffan; Deepa J. Arachchillage (Research and Practice in Thrombosis and Haemostasis, 2025)
Background: Myeloproliferative neoplasms (MPNs) represent a group of blood disorders characterized by myeloid cell proliferation and an associated increased risk of thrombosis and bleeding. Platelet count may have a direct link to these complications. Objectives: To share our MPN clinic’s experience with hemostatic testing and bleeding outcomes in patients with platelets ≥ 800 × 109/L. Methods: This was a single-center retrospective study from May 2022 to September 2024. Clinical characteristics, treatments, and bleeding events of patients with MPN or chronic myeloid leukemia were recorded. Laboratory assessments included full blood count, renal function, coagulation profiles, platelet function test, and von Willebrand factor (VWF) assays. Results: A total of 39 patients were included, majority of whom received aspirin for thrombosis prevention (76%). The study found that bleeding complications occurred in 33% of patients, with mucocutaneous bleeding being the most common. There was a trend toward bleeding in patients on aspirin (P = .07). However, platelet count alone did not predict bleeding risk. While some patients showed abnormal VWF function, low VWF levels were not consistently associated with increased bleeding. Interestingly, we found moderate negative correlation between baseline VWF ristocetin/antigen and activated partial thromboplastin time (P = .02; r = −.37) and prothrombin time (P = .009, r = −.45), suggesting other potential coagulation imbalances associated with bleeding diathesis in MPNs. Post cytoreduction, there was a significant increase in mean VWF ristocetin/antigen ratio (P = .0009). Conclusion: The study illustrates the limitations of relying solely on platelet counts to estimate bleeding risk in MPN patients. Assessment of VWF activity and careful selection of antithrombotic therapy were highlighted as important considerations.